Spiritual Quest of the Protagonist in Jack Kerouac’s The Dharma Bums - Poudel, Dinesh Kumar (Adhyayan Journal, 2023)
This article deals about the spiritual journey of Ray Smith to attain enlightenment with which he aims to bring salvation to all beings. As the guidelines of the journey is from Mahayana Buddhism, the seeker devotes his time in the activities apparently following the scripture. On his way ahead the seeker achieves the mental solace, arrives in the state of detachment. But as the seeker makes many appropriations to the religion, takesas alternative path to the corporate culture with the hope whereindividuals can live and grow free of sufferings. As a result, the journey does not yield the fruit as the seeker intends. The article focuses on ways the seeker strives and the outcome of the effort.